Beneficial Contribution of Alloy Disorder to Electron and Phonon Transport in Half‐Heusler Thermoelectric Materials. (30th April 2013) - Xie, Hanhui; Wang, Heng; Pei, Yanzhong; Fu, Chenguang; Liu, Xiaohua; Snyder, G. Jeffrey; Zhao, Xinbing; Zhu, Tiejun
Abstract Electron and phonon transport characteristics determines the potential of thermoelectric materials for power generation or refrigeration. This work shows that, different from most of high performance thermoelectric materials with dominant acoustic phonon scattering, the promising ZrNiSn based half‐Heusler thermoelectric solid solutions exhibit an alloy scattering dominated charge transport. A low deformation potential and a low alloy scattering potential are found for the solid solutions, which is beneficial to maintain a relatively high electron mobility despite of the large effective mass, and can be intrinsic favorable features contributing to the noticeably high power factors of ZrNiSn based alloys. A quantitive description of the different phonon scattering mechanisms suggests that the point defect scattering is the most important mechanism that determines the phonon transport process of the solid solutions. The present results indicate that alloying can be an effective approach for such materials systems to enhance thermoelectric figure of merit ZT by reducing phonon thermal conductivity, while minimizing the deterioration of charge mobility due to the low alloy scatteirng potential.